'Loss of efficacy of topical 5% permethrin for treating scabies: an Austrian single-center study'. (17th February 2022) - Meyersburg, Damian; Kaiser, Andreas; Bauer, Johann Wolfgang
Abstract: Background: Scabies is a contagious, itchy, parasitic infection of the skin. It is transmitted by skin-to-skin contact or by contact with contaminated material. Recent observations, especially in the outpatient setting, suggest there is decreasing efficacy of the standard treatment of choice, topical 5% permethrin cream. Objectives: To assess the efficacy and safety of topical permethrin for scabies treatment in patients. Methods: Patients visiting the Dermatology outpatient clinic with dermatoscopy-assured scabies were assessed for enrollment in the study. In total, 55 patients were enrolled and sequentially randomized into three groups. Group (A) received permethrin 5% cream on two occasions within a one-week interval, while (intensive) group (B) received the same administration of permethrin 5% cream plus the daily application of the cream on dermatoscopically verified affected sites (hands and/or genitals and/or feet). The treatment was evaluated at 3 weeks by dermatoscopy. Group A patients who failed to respond were allowed to repeat the treatment according to the group B scheme and were again evaluated after 3 weeks (group C). Results: Two applications of permethrin 5% cream (group A) produced a cure rate of 29% at follow-up. The intense application of permethrin 5% cream (group B) was not superior at follow-up (cure rate 31%). Patients who were retreated according to the intense scheme (group C) did not benefit at all. Conclusion: Mite populations with reduced susceptibility to permethrin exist in Austria and necessitate the evaluation of alternative treatment regimens. Key Messages: Human scabies is a rising major public health issue worldwide and has been designated as a neglected tropical disease by the World Health Organization. Resistance to permethrin, the most widely prescribed first-line therapy for scabies is to date underreported. At present, treatment recommendations remain controversially discussed as official guidelines do not address current development of resistances, and therefore their clinical applicability is limited.